The Relationship Between Mothers' Knowledge and Behavior about Nutritional Status with the Incidence of Stunting - Bancin, Anggina; Aidha, Zuhrina; Ashar, Yulia Khairina (GLOBAL HEALTH SCIENCE GROUP, 2024)
Child health problems that are currently the top priority that the government wants to improve are regarding child growth and developm Child health problems that are currently the top priority that the government wants to improve are regarding child growth and development. Of the many growth and development problems that occur in children, one of the health problems is stunting. Stunting is short or very short based on height length according to age that is less than -2 standard deviations (SD) on the WHO growth curve that occurs due to irreversible conditions due to inadequate nutritional intake and/or recurrent/chronic infections that occur in the First 1000 Days of Life (HPK). This study aims to analyze the relationship between knowledge and behavior of mothers about nutritional status with the incidence of stunting in Binanga Boang Penanggalan Village. The type of research in this study is quantitative research, with a cross sectional design, the population in this study is 101 mothers of people who have toddlers in Penanggalan Binanga Boang village. The sampling technique uses accidental sampling technique. The research instrument uses questionnaires. Validity test on the mother's knowledge variable of 15 questions there are 10 valid questions, on the mother's behavior variable of 12 questions there are 10 valid questions. After testing the reliability of the questions which were declared valid, all questions from the knowledge and behavior variables were declared reliable or (alpha symbol) >0.6. The number of samples in this study was 40 mothers who had toddlers at the sun posyandu. Data analysis was performed with the ChiSquare test. The results of this study showed that there was a significant relationship between maternal knowledge and the incidence of stunting in Binanga Boang Penanggalan Village (p = 0.000). There is a significant relationship between maternal behavior and the incidence of stunting in Penanggalan Binanga Boang village (p = 0.000). It is recommended for Poskesdes to increase public knowledge through preventive measures and health promotion to the community and increase counseling on stunting to pregnant women, adolescents, or catin. And for the community, especially parents who have toddlers to participate more in every activity held by the Puskesmas. ent. Of the many growth and development problems that occur in children, one of the health problems is stunting. Stunting is short or very short based on height length according to age that is less than -2 standard deviations (SD) on the WHO growth curve that occurs due to irreversible conditions due to inadequate nutritional intake and/or recurrent/chronic infections that occur in the First 1000 Days of Life (HPK). This study aims to analyze the relationship between knowledge and behavior of mothers about nutritional status with the incidence of stunting in Binanga Boang Penanggalan Village. The type of research in this study is quantitative research, with a cross sectional design, the population in this study is 101 mothers of people who have toddlers in Penanggalan Binanga Boang village. The sampling technique uses accidental sampling technique. The research instrument uses questionnaires. The number of samples in this study was 40 mothers who had toddlers at the sun posyandu. Data analysis was performed with the ChiSquare test. The results of this study showed that there was a significant relationship between maternal knowledge and the incidence of stunting in Binanga Boang Penanggalan Village (p = 0.000). There is a significant relationship between maternal behavior and the incidence of stunting in Penanggalan Binanga Boang village (p = 0.000). It is recommended for Poskesdes to increase public knowledge through preventive measures and health promotion to the community and increase counseling on stunting to pregnant women, adolescents, or catin. And for the community, especially parents who have toddlers to participate more in every activity held by the Puskesmas.